Investigation into management’s reluctance in implementing audit recommendations and its effects to risk: case Study of Civil Service Commission - Jawi, Daniel (Midlands State University, 2014)
Jackson and Stent (2010) describes an, Auditor as an independent expert whose primary responsibility is to express an independent opinion on whether the financial statements show a true and fair view. An auditor identifies and evaluates risks which may affect financial statements assertions. In addition to an expression of an opinion, Auditors also provide very useful recommendations in response to identified risks. When an audit recommendation is made to an organisation basically its management is responsible for the implementation. If management decides not to implement audit recommendations, risks will remain according to www.anao.gov.au. Study findings revealed that Civil Service Commission (CSC), which is a Government institution, was not managing risk more effectively as evidenced by the recurrence of same audit observations and the non-implementation of audit recommendations within the agreed time frames. Jackson and Stent (2010) said management is responsible for managing risks.CSC was experiencing serious challenges in the accountability of public funds. This study therefore sought to investigate into management’s reluctance in implementing audit recommendations at CSC. The Citizenry demands good accountability and the efficient use of public money from those to whom delegated authority of managing public funds and resources has been conveyed to. Public money should be properly accounted for in terms of The Constitution of Zimbabwe and The Public Finance Management Act and the Auditor-General is required by law to examine all public accounts for at least once every year. Directors and management should therefore make sure that adequate measures which safeguard public money and property from abuse and wasteful allocation are in place and they should take heed of the Auditor-General and Internal audit recommendations in order to correct defects in the management of public funds. The non- implementation of audit recommendations was exposing the Civil Service Commission to wide risk factors which included the misappropriation of public funds, fraudulent activities and wasteful spending of public funds. The objectives of the study was to establish what were the major causes of reluctance in the implementation of audit recommendations which safeguards public funds at CSC and to provide recommendations which will help CSC to overcome reluctance towards the implementation of audit recommendations. The major findings were obtained through questionnaires and interviews and major findings revealed that non-implementation of audit recommendations was being caused by the lack of management support and commitment towards the implementation of audit recommendations and also due to the absence of an audit committee which in turn compromise the independence of auditors. The study recommended that the Civil Service Commission should speed up efforts towards the establishment of an audit committee and there is also need for the update of the current legal frameworks so as to give more sanction powers to the Auditor –General to allow him/her to monitor the implementation of audit recommendations by Ministries as observed by Zinyama (2013). The identified legal instruments which required updates were the Constitution of Zimbabwe, The Public Finance Management Act and The Audit Office Act. Study also recommended that CSC should adopt International Public Sector Accounting Standards (IPSAS) as they help to improve transparency and good accountability of public funds.